2014
DOI: 10.1093/mnras/stu2196
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between hard gamma-ray sources and cosmic voids along the line of sight

Abstract: We estimate the galaxy density along lines of sight to hard extragalactic gamma-ray sources by correlating source positions on the sky with a void catalog based on the Sloan Digital Sky Survey (SDSS). Extragalactic gamma-ray sources that are detected at very high energy (VHE; E > 100 GeV) or have been highlighted as VHE-emitting candidates in the F ermi Large Area Telescope hard source catalog (together referred to as "VHE-like" sources) are distributed along underdense lines of sight at the 2.4σ level. There … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 44 publications
4
48
0
Order By: Relevance
“…Individual EBL levels should essentially be compatible with each other as the EBL is assumed to be a diffuse isotropic background. Potential anisotropies of the EBL (Furniss et al 2015;Abdalla & Böttcher 2017) are estimated to be beyond the sensitivity of this EBL measurement method. The dispersion of individual values can reflect systematic uncertainties and potential limitations of the procedure.…”
Section: Spectrally Resolved Ebl Levelsmentioning
confidence: 99%
“…Individual EBL levels should essentially be compatible with each other as the EBL is assumed to be a diffuse isotropic background. Potential anisotropies of the EBL (Furniss et al 2015;Abdalla & Böttcher 2017) are estimated to be beyond the sensitivity of this EBL measurement method. The dispersion of individual values can reflect systematic uncertainties and potential limitations of the procedure.…”
Section: Spectrally Resolved Ebl Levelsmentioning
confidence: 99%
“…Possible solutions include the hypothesis that the EBL density is generally lower than expected from current models (Furniss et al 2013); the existence of exotic axion like particles (ALPs) into which VHE γ-rays can oscillate in the presence of a magnetic field, thus enabling VHE-photons to avoid γγ absorption (Dominguez et al 2011b); an additional VHE γ-ray emission component due to interactions along the line of sight of extragalactic ultra-high-energy cosmic rays (UHECRs) originating from the blazar (e.g., Essey & Kusenko 2010); and EBL inhomogeneities. The idea of EBL inhomogeneities was considered by Furniss et al (2015), who found tentative hints for correlations between hard VHE γ-ray sources and under-dense regions along the line of sight.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the authors of [26] proposed some alternative explanations to their findings in the paper itself. The significance of the effect observed in [28] is below 3 σ. As for [29], the result could in principle be explained by the scattering of electrons and positrons accelerated in the source by a stronger local magnetic field (B ∼ 10 −12 − 10 −7 G), in which case quasi-isotropic halos may form around the source [30].…”
Section: Electromagnetic Cascade Modelmentioning
confidence: 81%
“…Finally, fig. 13 presents several curves of the boost factor vs. energy labeled by different values of the fraction of space filled with voids -the so-called "voidiness" parameter [28]. It is interesting that at comparatively low values of voidiness (0.2-0.3) the values of K B are much larger at high energies than for the case of voidiness =1.…”
Section: Electromagnetic Cascade Modelmentioning
confidence: 99%